SPORTS, GENDER AND SUSTAINABLE DEVELOPMENT: THE LEGACY OF DISTRIBUTION "GENDERED" PRACTICES - ABALOT, EMILE JULES; WABI, SAKARIYAOU ALABI; ATTIKPA, ANTOINE; ATTIKLEME, KOSSIVI (My University, 2016)
This comparative study of sports practices from physical exercises and traditional games actually makes a contribution to current thinking giving understanding and perspective reflections tools that structured sports social courses in Francophone Black Africa, particularly those of women through different cultural areas. Meeting in this regard, several case studies, the approach tries to deepen three key dimensions which question successively access to sport inequality, diversity in social relations with the body and bodily practices in micro African companies that are rather conservatories the supremacy of a more traditional femininity. On these aspects, the criteria for inclusion and / or exclusion defined by reference to normality, physical, biological, and current or potential mental functions, transformations proximity regardless of the immediate socio-cultural environment and finally, opening of sports practices to new populations in situation of confrontation with the difference that Goffman (1975) calls the topics "discredited" are probably a few variables that this study used to make them more readable all the problems that use the body as a reflecting material for sustainable development. In addition to reports of positive discrimination that men and women (gender), maintain the sports field and behind the appearance of a dislocation of hierarchies transmitted in microphones African societies (without technical body of the use of complex ) must emerge a collective representation less stigmatizing the sexual distribution of body uses.
Keywords: Body; Sports; Kind; Small society; Development.